2016
DOI: 10.1111/jnc.13763
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibition reverses TDP‐43 effects on synaptic protein expression, astrocytic function and amino acid dis‐homeostasis

Abstract: The trans-activating response of DNA/RNA-binding protein (TDP)-43 pathology is associated with many neurodegenerative diseases via unknown mechanisms. Here, we use a transgenic mouse model over-expressing human wild-type neuronal TDP-43 to study the effects of TDP-43 pathology on glutamate metabolism and synaptic function. We found that neuronal TDP-43 over-expression affects synaptic protein expression, including Synapsin I, and alters surrounding astrocytic function. TDP-43 over-expression is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…To probe numerous analytes, we utilize the Luminex xMAP technology [11, 15, 17, 24]. Kidney injury analytes were measured in serum with the Mouse Kidney Injury Magnetic Bead Panel 1 (Cat MKI1MAG-94K, EMD Millipore).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To probe numerous analytes, we utilize the Luminex xMAP technology [11, 15, 17, 24]. Kidney injury analytes were measured in serum with the Mouse Kidney Injury Magnetic Bead Panel 1 (Cat MKI1MAG-94K, EMD Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Our group has previously shown that FDA-approved tyrosine kinase inhibitors (TKIs) nilotinib (Tasigna®) and bosutinib (Bosulif®) are potential therapeutics for neurodegenerative diseases [11-17]. These findings led to phase II clinical trials currently underway.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, lactate supplementation rescues motor neurons in co-culture with hSOD1 G93A astrocytes [74]. On the other hand, an increase in lactate levels has been described in the brain of a TDP-43 mouse model [105]. Regardless, a better understanding of the changes in astrocyte-neuron metabolic coupling in the disease may lead to therapeutic interventions aimed at enhancing astrocytic neuronal metabolic support.…”
Section: Pathways Involved In Astrocyte-mediated Motor Neuron Toximentioning
confidence: 99%
“…TDP-43 may also be involved in local translation in the synapse, translocating into dendrites in an activity-dependent manner (Wang, Wu, Chang, & Shen, 2008). Recently, we showed that TDP-43 controls mRNA expression of synaptic proteins such as synapsin I, leading to alterations in protein levels of synaptic proteins (Heyburn, et al, 2016). Together, the role of TDP-43 in regulation of gene expression is wide-reaching and disruption of TDP-43 in disease can affect all of these cellular processes, leading to cellular pathology.…”
Section: Tdp-43 and Rna-related Functionsmentioning
confidence: 99%
“…Another study using a Drosophila model shows that the Drosophila homolog of TDP-43, TBPH binds to and regulates the expression of the mRNA of syntaxin 1A, which is a vesicular protein involved in vesicular fusion and exocytosis (Romano, et al, 2014). Our group has found that TDP-43 controls the expression of the synaptic proteins synapsin I and synaptotagmin (Heyburn, et al, 2016). Overexpression of TDP-43 in neurons leads to decreased expression of these proteins, providing further evidence of the importance of TDP-43 for synaptic function (Heyburn, et al, 2016).…”
Section: Tdp-43 and Rna-related Functionsmentioning
confidence: 99%